2019
DOI: 10.1021/acs.orglett.8b03732
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Substituted Furans by a Cascade of Formal anti-Carbopalladation/Hydroxylation and Elimination

Abstract: Highly substituted furans are generated by a cascade of formal anti-carbopalladation, attack of a nucleophilic hydroxy group, and aromatization by elimination of the emerging dihydrofuran derivative. Mono-, di-, and trisubstituted furans were obtained in good to excellent yields. When we attempted to access tetrasubstituted furan derivatives, an additional rearrangement was observed that resulted in the formation of chromenes. Follow-up chemistry shows the utility of TMS as a protecting group for the alkyne mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…of DBU as the additive was added to the reaction mixture . Schitter's group reported that the reaction strictly relied on the presence of additive in the Pd‐catalyzed domino process involving a formal anti‐carbopalladation of internal alkynes . They believed that Et 3 N as the additive could facilitate the synthesis of substituted furans to get the good yields.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…of DBU as the additive was added to the reaction mixture . Schitter's group reported that the reaction strictly relied on the presence of additive in the Pd‐catalyzed domino process involving a formal anti‐carbopalladation of internal alkynes . They believed that Et 3 N as the additive could facilitate the synthesis of substituted furans to get the good yields.…”
Section: Introductionmentioning
confidence: 58%
“…[27] Schitter's group reported that the reaction strictly relied on the presence of additive in the Pd-catalyzed domino process involving a formal anti-carbopalladation of internal alkynes. [28] They believed that Et 3 N as the additive could facilitate the synthesis of substituted furans to get the good yields. What's more, Zhou et al proposed that the reaction yields can be effectively controlled by using different additives (C5H5NO (pyridine N-oxide) vs. PhNO (nitrosobenzene)) in the gold-catalyzed dehydrogenative annulation of 2-(1-alkynyl)-2-alken-1-ones under mild reaction conditions, and C5H5NO is the ideal additive for the construction of 2,3-furan-fused carbocycles.…”
Section: Introductionmentioning
confidence: 99%
“…20 By shortening the length of the tether connecting the alkyne and the hydroxy group to two carbon atoms, a broad variety of highly substituted furans 48 was accessed (Scheme 19). 21 The previously reported Pd-catalyzed domino process was extended by an elimination leading to aromatization. During the evaluation of the reaction conditions, we observed only traces of the product when we used the bidentate ligand dppe [1,2-bis(diphenylphosphino)ethane].…”
Section: Termination With Heteronucleophilesmentioning
confidence: 99%
“…However, when we tried to access tetrasubstituted furans, an unprecedented rearrangement occurred affording chromenes of type 50 (Scheme 20). 21 After the domino process, but before the elimination, the Pd seems to coordinate to the double bond forming allyl complex 52. This intermediate is able to rearrange into the corresponding intermediate 53.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…Pyrans and furans are important structural elements of many natural products and pharmaceuticals and valuable reaction precursors or intermediates in organic synthesis . There are several synthetic strategies which yield pyrans and furans bearing different substitution patterns. ,, One frequently used method involves cyclization or cycloaddition reactions of unsaturated carbonyl compounds using transition metal catalysts such as Hg, Au, Pd, Ag, Co, Zn, Cu, Rd, and Pt and other metals such as Ca, Ga, Sc, and Bi …”
Section: Introductionmentioning
confidence: 99%